Antibody response after COVID-19 vaccine BNT162b2 on health care workers in Japan - Yoshimura, Yukihiro; Sasaki, Hiroaki; Miyata, Nobuyuki; Miyazaki, Kazuhito; Tachikawa, Natsuo (Journal of infection and chemotherapy : official journal of the Japan Society of Chemotherapy, 2021)
Vaccination is one of the most important tools to control the COVID-19 pandemic. However, there is little information on the antibody response in humans after the COVID-19 vaccination. This single-center, prospective study was conducted in Yokohama, Japan. We included health care workers who had received two doses of COVID-19 vaccination (BNT162b2) 21 days apart. We measured serum immunoglobulin G (IgG) to nucleoprotein and spike protein of SARS-CoV-2 with commercially available kits before and 7, 14, and 35 days after the first dose of vaccination. A total of 104 workers participated in this study. Of these, 7 participants were seropositive with antibodies to spike protein at baseline and 4 of the 7 seropositive participants had COVID-19 history. The mean level of IgG to spike protein (QT) was 45.2, 1219, 2845, and 23489 AU/mL at baseline, on days 7, 14, and 35, respectively, although the values for nucleoprotein (NG) were 0.2, 0.21, 0.22, and 0.19 S/C, respectively. On day 7, QT in seropositive participants at baseline was elevated, whereas it was not elevated in seronegative participants at baseline until day 14. QT was elevated over the cutoff in all the participants at day 35, but NG did not change between baseline and day 35.